2001
DOI: 10.1074/jbc.m102057200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Significant Residues for Homoallylic Substrate Binding of Micrococcus luteus B-P 26 Undecaprenyl Diphosphate Synthase

Abstract: The primary structure of cis-prenyltransferase is totally different from those of trans-prenyltransferases (Shimizu, N., Koyama, T., and Ogura, K. (1998) J. Biol. Chem. 272, 19476 -19481). To better understand the molecular mechanism of enzymatic cis-prenyl chain elongation, we selected seven charged residues in the con- Prenyltransferases, also referred to as prenyl diphosphate synthases, are enzymes catalyzing the sequential condensation of isopentenyl diphosphate (IPP) 1 with allylic diphosphates to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…This structural P-loop is supposed to interact with the pyrophosphate of the allylic substrate FPP. A second binding site for pyrophosphate of the homoallylic substrate IPP was also proposed (10,16 A and B, two orthogonal views of the enzyme with bound sulfate, magnesium ions, and Triton X-100 molecules. The left monomer, A, is colored in red and green for ␣-helices and ␤-strands, respectively, whereas the right monomer, B, is in magenta and cyan, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This structural P-loop is supposed to interact with the pyrophosphate of the allylic substrate FPP. A second binding site for pyrophosphate of the homoallylic substrate IPP was also proposed (10,16 A and B, two orthogonal views of the enzyme with bound sulfate, magnesium ions, and Triton X-100 molecules. The left monomer, A, is colored in red and green for ␣-helices and ␤-strands, respectively, whereas the right monomer, B, is in magenta and cyan, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…2B shows the detailed arrangement of these amino acids. This region has been suggested as the FPP-and IPP-binding site based on site-directed mutagenesis studies (24,36).…”
Section: Resultsmentioning
confidence: 99%
“…GPP, FPP, as well as GGPP all proved to serve as substrates for AtCPT7 and exhibited Michaelian kinetics at saturating concentrations of 14 C-IPP ( Figure 3C). However, steady state kinetic analysis revealed that the enzyme had a 10-fold preference for GGPP and FPP compared with GPP (Table 1), with kinetic constants that fell within the range reported for other plant and bacterial CPTs (Kharel et al, 2001;Schulbach et al, 2001;Guo et al, 2005;Schilmiller et al, 2009;Kera et al, 2012;Demissie et al, 2013). This point was further clarified by structural analysis ( 1 H NMR) of Pren-10 (the dominating polyprenol in leaf tissue; Figure 1C) isolated from the leaves of wild-type Arabidopsis (Supplemental Figure 9).…”
Section: Recombinant Atcpt7 Enzyme Activity and Substrate Specificitymentioning
confidence: 99%